Beer enrichment with biologically active hop compounds - Protsenko, Lidia; Rudyk, Ruslan; Hryniuk, Tetiana; Vlasenko, Aliona; Protsenko, Alona; Litvynchuk (Vorontsova), Svitlana; Ovadenko, Olena (My University, 2018)
Combined use of the Slavyanka hop variety and the Ruslan and Xantha hops in the suggested ratio enriches the drink with biologically active hop compounds, thus improving its functionality.
Keywords: hop; beer; hanthohumol; beta-acids; polyphenols; хміль; пиво; ксантогумол; бета-кислоти; поліфеноли; кафедра фізики та професійної безпеки